The impact of IFRS adoption and IFRS readiness on businesses’ global value chain participation: A case study in Vietnam - Phan, Thi Anh Dao; Tran, Huong Thi Thanh; Nguyen, Thi Quynh Hoa; Hoang, Thanh Huyen; Le, Ha Thi Thu (Edelweiss Applied Science and Technology, 2026)
In the context of globalization and the restructuring of global value chains (GVCs), active engagement in GVCs is viewed as a vital way for companies in emerging economies to improve their competitiveness. In addition to the conventional factors of scale and technology, International Financial Reporting Standards (IFRS) are increasingly becoming important in facilitating the engagement of companies with international partners. However, there is a lack of empirical evidence at the enterprise level regarding the relationship between IFRS and GVC integration, particularly in the context of developing countries like Vietnam. The purpose of this study is to explore the effect of International Financial Reporting Standards (IFRS) on the extent of integration into GVCs of businesses in Vietnam. Based on survey data from 177 businesses and employing both Ordinary Least Squares (OLS) estimation and Bayesian modeling (MCMC), we find that the adoption of IFRS and the level of readiness to adopt IFRS have a significant positive effect on the ability of businesses to deeply engage in GVCs. Moreover, technological capability is an important driving force in this process. This study has significant implications for policymakers in promoting the IFRS adoption roadmap to improve the competitiveness of businesses.